Skeletal Muscle Hypertrophy and Decreased Intramuscular Fat After Unilateral Resistance Training in Spinal Cord Injury: Case Report - Gorgey, Ashraf S (American Paraplegia Society, 2010)
BACKGROUND: Skeletal muscle atrophy is a common adaptation after spinal cord injury (SCI) that results in numerous health-related complications. Neuromuscular electrical stimulation (NMES) has been recognized as an effective tool, which attenuates atrophy and evokes hypertrophy. OBJECTIVE: To investigate the effects of NMES resistance training (RT) on individual muscle groups and adipose tissue of the right thigh after stimulation of the knee extensor muscle group in a man with chronic SCI. PARTICIPANT: A 22-year-old man with a complete SCI sustained in a motorcycle accident 5 years prior to participation in this study. METHODS: The participant underwent training twice a week for 12 weeks, including unilateral progressive RT of the right knee extensor muscle group using NMES and ankle weights. The stimulation was applied to knee extensors while the participant was sitting in his wheelchair. A series of T1-weighted magnetic resonance images were acquired for the whole right thigh prior to and after training. Skeletal muscle cross-sectional areas were measured of the whole thigh, knee extensors, hip adductors, hamstrings, and sartorius and gracilis muscle groups. Additionally, intramuscular fat and subcutaneous fat of the thigh were measured. RESULTS: At the end of 12 weeks, the participant was able to lift 17 lbs during full knee extension. Average skeletal muscle cross-sectional areas increased in all of the measured muscle groups (12%–43%). Hypertrophy ranging from 30% to 112% was detected in multiaxial slices after the NMES RT protocol. Intramuscular fat decreased by more than 50% and subcutaneous fat increased by 24%. CONCLUSION: Unilateral NMES RT protocol evoked hypertrophy in the knee extensor and adjacent skeletal muscle groups and was associated with a reduction in intramuscular fat in a person with a chronic SCI. Additionally, subcutaneous adipose tissue cross-sectional areas increased in response to RT.